2017
DOI: 10.1115/1.4037679
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Various Pressure Based Boundary Conditions for Three-Dimensional Subsonic DSMC Simulation

Abstract: Three-dimensional (3D) direct simulation Monte Carlo (DSMC) has been used to simulate flow in a straight microchannel using an in-house parallelized code. In the present work, a comparative study of seven boundary conditions is carried out with respect to time required for achieving steady-state, accuracy in predicting the specified pressure at the boundaries, and the total simulation time required for attaining a statistical error within one percent. The effect of changing the Knudsen number, pressure ratio (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Additionally, a novel collision scheme, known as the simplified Bernoulli trial, has been introduced in Stefanov (2011). The DSMC technique has also been employed in Gavasane et al (2011Gavasane et al ( , 2017, Jadhav et al (2017), Shah, Agrawal & Bhandarkar (2018a, Shah et al (2018b) andJadhav, Gavasane & for different microchannel flow and shock wave problems. That is why we also resort to DSMC data to validate the analytical solution obtained above.…”
Section: Validation Of Analytical Solution Using Dsmc Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a novel collision scheme, known as the simplified Bernoulli trial, has been introduced in Stefanov (2011). The DSMC technique has also been employed in Gavasane et al (2011Gavasane et al ( , 2017, Jadhav et al (2017), Shah, Agrawal & Bhandarkar (2018a, Shah et al (2018b) andJadhav, Gavasane & for different microchannel flow and shock wave problems. That is why we also resort to DSMC data to validate the analytical solution obtained above.…”
Section: Validation Of Analytical Solution Using Dsmc Datamentioning
confidence: 99%
“…(2017), Shah, Agrawal & Bhandarkar (2018 a ), Shah et al. (2018 b ) and Jadhav, Gavasane & Agrawal (2021) for different microchannel flow and shock wave problems. That is why we also resort to DSMC data to validate the analytical solution obtained above.…”
Section: Analytical Solution Of Pressure-driven Poiseuille Flowmentioning
confidence: 99%
“…Their results showed that the pressure distribution was related to the flow direction and the normal position of the wall, and obtained the distribution expression of gas flow pressure in the microchannel. Shah et al [91] used the DSMC method to simulate the nitrogen flow in the straight microchannel under seven different boundary conditions. Their results presented that the pressure, velocity and translation temperature of microchannels under different boundary conditions would have the same variation trend.…”
Section: Molecular Dynamic Simulation (Mds) and Direct Simulation Mon...mentioning
confidence: 99%
“…where n f is the gas number density at [12,22,23,30,35,36]. A value of N ppc = 10 was used for results presented in the current study.…”
Section: Boundary Conditionsmentioning
confidence: 99%